Testicular hypoplasia in a bull with XX/XY chimerism - Bongso, Tuan Ariffeen; Jainudeen, Mohamed Razeen; Lee, J. Y. (New York State College of Veterinary Medicine, 1981)
A 4-year-old 1/2 Hereford X Bos indicus bull displayed XX/XY chimerism associated with arrested spermatogenesis. Phenotypic examination revealed underdeveloped dorsal neck muscles, a non-pendulous scrotum, testes firm in consistency and a scrotal circumference measurement of 27 cm. On rectal palpation, small seminal vesicles were present and only azoospermic seminal fluid was collected at 3 monthly electroejaculations. Chromosome analysis on 2 monthly batches of leukocyte cultures showed a mean chimeric ratio of 80% of XX:20% XY cells. Cells cultured from skin were all male. Histopathological examination of both testes revealed reduction in size and number of tubules, marked hypoplastic germinal epithelium showing only spermatogonia and a well defined interstitium with large quantities of collagen. The small size of the testes and histological changes were suggestive of a testicular hypoplasia.